PENGARUH PEMBERIAN EKSTRAK JAHE DENGAN KEJADIAN MUAL DAN MUNTAH PADA IBU HAMIL TRIMESTER I DI WILAYAH KERJA PUSKESMAS SUKARAME BANDAR LAMPUNG - Lidya Ariyanti; Rachmi Fitria Sari (Malahayati Nursing Journal, 2020)
EFFECT OF GINGER WITH SELLING MEDICAL AND EVEN THOUGHT IN PREGNANT WOMAN TRIMESTER I IN PUBLIC HEALTH  SUKARAMEBANDAR LAMPUNG CITY IN 2019 Introduction: Data from the Provincial Health Office of Lampung that the incidence of hyperemesis gravidarum in 2015-2016 is 385 people from 2093 pregnant women. Based on Lampung Province Health Profile in 2016 the high incidence of emesis gravidarum in pregnant women is 50-90%, while hyperemesis gravidarum reaches 10-15% in Lampung Province from the number of pregnant women there are as many as 186,319 people. The purpose of this research is to know the effect of  Ginger with the incidence of nausea and vomiting in first trimester pregnant women in public health sukarame Bandar Lampung City in 2018.Objective: It is know the effect of ginger extract consumption on first trimester pregnant women in reducing nausea and vomiting in public health sukarame Bandar Lampung city in 2019.Method: Quantitative research, quasi experimental design. The population was all pregnant women trimester 1 was 98. Samples was 30 women. Independent variable ginger extract. Dependent variable nausea vomiting in Pregnant Women. Data analysis was done by univariate (mean) and bivariate (t-test).Result: The results of the study found the average value of nausea and vomiting before given ginger extract is 13 times. The average value of nausea and vomiting after given ginger extract is 9 times. Effect of decreased nausea and vomiting in pregnant women trimester I (t-test t arithmetic, p-value 0.05). (T-test 13,135, p-value 0,05) with difference of decrease of value average 3 times. It is expected that pregnant women do not forget to consume drugs to reduce nausea and vomiting given. It is necessary to conduct an activity by health personnel such as counseling about the benefits of ginger extract, early detection of danger signs in young pregnancies, and others. Activities that run (posyandu) should be improved so that it can control the health of mothers especially to pregnant women. Keywords: ginger extract, nausea vomiting in Pregnant Women ABSTRAKPENGARUH PEMBERIAN EKSTRAK JAHE DENGAN KEJADIAN MUAL DAN MUNTAH PADA IBU HAMIL TRIMESTER I DI WILAYAH KERJAPUSKESMAS SUKARAME BANDAR LAMPUNGTAHUN 2019Pendahuluan: Data Dinkes Provinsi Lampung bahwa angka kejadian hiperemesis gravidarum pada tahun 2015- 2016 sebanyak 385 orang dari 2093 pasien ibu hamil. Berdasarkan Profil Kesehatan Propinsi Lampung tahun 2016 tingginya angka kejadian emesis gravidarum pada wanita hamil yaitu 50-90%, sedangkan hiperemesis gravidarum mencapai 10-15% di Propinsi Lampung dari jumlah ibu hamil yang ada yaitu sebanyak 186.319 orang..Tujuan: Diketahui pengaruh konsumsi ekstrak jahe pada ibu hamil Trimester I dalam mengurangi mual muntah di Puskesmas Sukarame Bandar Lampung Tahun 2019.Metode: Penelitian kuantitatif, rancangan quasi eksperiment. Populasi adalah seluruh ibu hamil trimester I sebanyak 98. Sampel sebanyak 30 ibu hamil trimester I Analisa data dilakukan dengan univariat (mean) dan bivariat (t-test). Variabel independen ekstrak jahe. Variabel dependen mual muntah pada Ibu Hamil.Hasil: Hasil Penelitian didapati rata-rata nilai mual dan muntah sebelum diberikan ekstrak jahe adalah 13 kali. Rata-rata nilai mual dan muntah setelah diberikan ekstrak jahe adalah 9 kali. Ada Pengaruh penurunan mual dan muntah pada ibu hamil trimester I (t-test t hitung, p–value 0,05). (t-test 13,135,p–value 0,05) dengan selisih penurunan nilai rata-rata 3 kali. Diharapkan ibu hamil tidak lupa untuk mengkonsumsi obat untuk mengurangi mual dan muntah yang diberikan. Perlu diadakan suatu kegiatan oleh tenaga kesehatan seperti penyuluhan tentang manfaat ektrak jahe, pendeteksian secara dini tanda bahaya pada kehamilan muda, dan lain-lain. Kegiatan yang berjalan (posyandu) harus lebih ditingkatkan sehingga mampu mengontrol kesehatan ibu terlebih kepada ibu hamil. Kata kunci : ektrak jahe, mual muntah ibu hamil.